THE ROLE OF SUBDISTRICT HEAD (CAMAT) IN EARTHQUAKE DISASTER MANAGEMENT: A Case Study in Garut Regency - Martini, Ani; Setyasih, Endang Try; Simanjuntak, Nelson; Karmila, Cut Laila; Poniman, Ade; Sugiani, Deni; Tahir, M. (Department of Government, FISIP, Universitas Padjadjaran, 2025)
The September 18, 2024, earthquake in Garut Regency, West Java, Indonesia, highlighted the crucial role of subdistrict heads (Camat) in disaster management. This study explores their role in coordinating and collaborating with various stakeholders, identifying challenges, and evaluating their effectiveness. The research emphasizes the Camat's leadership in mobilizing resources, facilitating inter-agency coordination, and engaging communities to ensure a swift and effective disaster response. Findings reveal significant barriers, including bureaucratic inefficiencies and limited resources, but also highlight successful strategies employed by Camat to overcome these challenges. The study concludes with actionable recommendations to enhance disaster management practices in Indonesia's decentralized governance frameworkgb777